Promotion of cytotoxic T-cell generation in mixed leukocyte culture by phosphatidylinositol-specific phospholipase C from Bacillus thuringiensis. - Rahman, S M (1995)
Phosphatidylinositol-specific phospholipase C (PIPLC) from Bacillus thuringiensis, which cleaves phosphatidylinositol or glycosylphosphatidylinositol on the external cell surface to generate a second messenger for intracellular signal transduction (S. Rahman et al., FEBS Lett. 303:193-196, 1992), was found to preferentially promote the generation of alloantigen-specific cytotoxic T lymphocytes in mixed leukocyte culture. PIPLC affected an early stage of cytotoxic T-lymphocyte activation in culture, and there was no evidence of any soluble cellular mediators of this PIPLC action. PIPLC neither enhanced overall cell proliferation nor noticeably promoted interleukin-2 and -4 production in mixed leukocyte culture. The relative population size of Ly-2+ T cells was increased, however, in a late mixed leukocyte culture with PIPLC. In addition, PIPLC enhanced an anti-CD3 monoclonal antibody-induced early increase in [Ca2+]i. These results suggest a new parasite (bacterium)-oriented mechanism for enhancing antigen-driven host cytotoxic T-lymphocyte immunity which does not include promotion of interleukin-2 production.